2017
DOI: 10.1038/s41598-017-07908-z
|View full text |Cite
|
Sign up to set email alerts
|

Small amphipathic peptides are responsible for the assembly of cruciferin nanoparticles

Abstract: Amphipathic peptides are versatile building blocks for fabricating well-ordered nanostructures, which have gained much attention owing to their enormous design possibilities and bio-functionalities. However, using amphipathic peptides from natural proteins to create tunable nanostructures is challenging because of their heterogeneity and great tendency to form aggregates. Here we fabricated two well-defined nanoparticles from cruciferin amphipathic peptides by integrating top-down and bottom-up approach. Alkal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…2C &D) (Barber et al 2017). The gB, gC, and gD proteins had been validated as subunit vaccine candidates and conferred significant protection from BoHV-1 challenge when formulated with an effective adjuvant(* 1997; Blanc et al 2012;J. CHARLES WHITBECK 1988;Keil et al 2005;Keil et al 2010;Levings et al 2015; M.J. Kaashoek'" and Oirschot*$ 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2C &D) (Barber et al 2017). The gB, gC, and gD proteins had been validated as subunit vaccine candidates and conferred significant protection from BoHV-1 challenge when formulated with an effective adjuvant(* 1997; Blanc et al 2012;J. CHARLES WHITBECK 1988;Keil et al 2005;Keil et al 2010;Levings et al 2015; M.J. Kaashoek'" and Oirschot*$ 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, selecting biodegradable nanoparticles to replace the PS nanoparticles will be our ultimate aim. Biodegradable nanomaterials [e.g., dextran, poly (lactic-co-glycolic acid), chitosan, polyethylene glycol, pullulan, and peptides] have been applied in drug delivery and cancer therapy because of their safety and degradation characteristics in vivo (Brewer et al 2017;Gheibi Hayat and Darroudi 2019;Ho et al 2018;Hong et al 2017;Jiang et al 2013;Liang et al 2019;Mona Gupta 2004;Xiaobo Fan1 et al 2016). Thus, these materials may be candidates for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Turbidity is caused by the protein aggregation and is an index of the solubility of protein hydrolysates (Xiong, ). The average particle size and zeta potential in a 2 mg/mL solution of EWH and HPH were measured using a Malvern Nanosizer ZS instrument (Malvern Inc., Malvern, UK) at 25 °C as previously reported (Hong, Akbari, & Wu, ). Disposable folded capillary cells (DTS 1070) were filled slowly to avoid air bubbles.…”
Section: Methodsmentioning
confidence: 99%
“…The results suggested that cruciferin can be used for preparing particles and delivering bioactives using the cold gelation method (Akbari & Wu, ). In a complementary study, Hong et al () found that amphipathic peptides with 5–22 amino acid residues were responsible for the particle formation. These amphipathic peptides primarily adopted the β‐sheet and turn conformations.…”
Section: Protein‐based Delivery Systemsmentioning
confidence: 99%
“…These limitations have prompted other novel uses of CP for preparing plastics (Manamperi, Chang, Ulven, & Pryor, ), adhesives (Bandara, Esparza, & Wu, ; Li, Qi, Sun, et al, ; Li, Qi, Sun, & Wang, ; Wang et al, ), self‐assembled nanoparticles (Hong, Akbari, & Wu, ), and in targeted delivery applications (Akbari & Wu, ; Akbari & Wu, ). Emerging interest on such nonfood applications in potential value‐added utilization is essential to improve the sustainability and profitability of the canola industry.…”
Section: Introductionmentioning
confidence: 99%